Brain-derived neurotrophic factor in VMH as the causal factor for and therapeutic tool to treat visceral adiposity and hyperleptinemia in type 2 diabetic Goto–Kakizaki rats - Maekawa, Fumihiko; Fujiwara, Ken; Toriya, Masako; Maejima, Yuko; Nishio, Takashi; Toyoda, Yukiyasu; Nohara, Keiko; Yashiro, Takashi; Yada, Toshihiko (Frontiers in Synaptic Neuroscience, 2013)
We previously reported that the type 2 diabetic Goto-Kakizaki (GK) rats at young adult ages (6-12 weeks) exhibited increased visceral fat mass and hyperleptinemia, due to hyperphagia caused primarily by neuropeptide Y (NPY) overexpression in the hypothalamic arcuate nucleus. Later, we found that GK rats continued to exhibit mesenteric fat accumulation and hyperleptinemia at least until 26 weeks of age, while hyperphagia and NPY overexpression ceased at 15 weeks of age. Therefore, we hypothesized that the long-lasting fat accumulation and hyperleptinemia are due to unidentified brain dysfunction other than NPY overexpression. In GK rats aged 26 weeks, glucose transporter-2 (GLUT2) mRNA expression in ventromedial hypothalamus (VMH) was markedly reduced in parallel with significant decreases in brain-derived neurotrophic factor (BDNF) mRNA level and BDNF-expressing cell numbers in the VMH. Pharmacologic inhibition of glucose utilization reduced BDNF mRNA expression in VMH in vivo and in vitro. The results suggested that impaired glucose utilization caused the reduction of BDNF. On the other hand, intracerebroventricular injection of BDNF for 6 days ameliorated hyperleptinemia in a long-lasting manner concurrently with feeding suppression in GK rats. Restricted feeding paired to BDNF-treated rats reduced plasma leptin level only transiently. BDNF treatment also reduced mesenteric fat mass in GK rats. These results reveal a novel action mode of BDNF to long-lastingly counteract visceral adiposity and hyperleptinemia in addition to and independently of its anorexigenic action. These results suggest that visceral fat accumulation and hyperleptinemia are at least partly due to the reduction of BDNF in VMH primarily caused by impaired glucose utilization in GK rats. The BDNF supplementation could provide an effective treatment of visceral obesity, hyperleptinemia and leptin resistance in type 2 diabetes.